Measurement and Convergence Analysis of the Development Level of Marine New Quality Productive Forces in China - SHE Hongyan; WANG Xujian (Haiyang Kaifa yu guanli)
Developing marine new quality productive forces is an inherent demand and important focus for promoting high-quality development of the marine economy, and is of great significance for accelerating the construction of a maritime power. Based on the panel data of 11 coastal provinces (autonomous regions, centrally administered municipalities) in China from 2011 to 2021, this paper constructs an evaluation index system for the development level of China’s marine new quality productive forces, uses the entropy method to calculate and analyze, and uses Dagum Gini coefficient and convergence model to analyze the regional differences and convergence characteristics of the development of marine new quality productive forces. The results show that: firstly, the overall development level of marine new quality productive forces in the coastal areas of China and the three major marine economic circles of the north, east, and south shows a fluctuating upward trend, but there are obvious regional differences, and the development level shows a decreasing trend from south to east to north; Secondly, the overall regional differences in the development level of marine new quality productive forces are showing a downward trend. The internal differences within the southern marine economic circle are the largest, the internal differences within the eastern marine economic circle are the smallest, and the regional differences between the northern and southern marine economic circles are the most obvious. The contribution rate of super density is the main source of regional differences; Thirdly, there is a σ convergence in the new marine productivity of the eastern and southern marine economic circles; There is absolute β convergence in the northern and eastern regions, and significant conditional β convergence exists in the overall coastal areas of China, as well as in the northern and eastern marine economic circles.